Screening of Bioactive Fraction of Radix Paeoniae Alba and Enhancing Anti-Allergic Asthma by Stir-Frying Through Regulating PI3K/AKT Signaling Pathway - Xia'nan Sang; Jialiang Ying; Xuedong Wan; Xin Han; Qiyuan Shan; Qiang Lyu; Qiao Yang; Kuilong Wang; Min Hao; Erlong Liu; Gang Cao (Frontiers Media S.A., 2022)
Allergic asthma is a common respiratory inflammation disease. The crude Radix Paeoniae Alba (RPA) and its processed products have been used frequently as antipyretic and anti-inflammatory agents in traditional medicine. To evaluate the effect of honey and bran processing, different fractions of RPA were used for treating anti-allergic asthma in the ovalbumin (OVA)-induced mice model, and then, the most effective fraction of RPA and stir-frying Radix Paeoniae Alba with honey and bran (FRPA) for treating anti-allergic asthma were compared mutually for pharmacological effects. The results showed that the treatment of the dichloromethane fraction of RPA significantly improved the pathological condition of lung tissues, decreased the number of eosinophils and other cells in bronchoalveolar lavage fluid (BALF), and the increased the expression of various inflammatory factors. Furthermore, the study discovered that the lung pathological conditions, compared with the high dose of dichloromethane RPA fraction, could be ameliorated by high dose of dichloromethane FRPA fraction treatment. Moreover, the expression of inflammatory factors and the phosphorylation of the PI3K/AKT signaling pathway could be diminished by FRPA. Finally, the contents of compounds with a significant difference in the FRPA dichloromethane fraction were paeoniflorin, ethyl gallate, pentagalloylglucose, galloylpaeoniflorin, and others by UPLC/Q-TOF-MS analysis. These findings suggest that the dichloromethane fraction of FRPA has an enhancement effect on anti-allergic asthma and provide the experimental basis for exploring the processed mechanism of RPA.